MEMAKNAI KEKHILAFAN HAKIM DALAM PUTUSAN NOMOR 308 K/Pdt.Sus-PHI/2018 - Mustika Prabaningrum Kusumawati (Faculty of Law, Parahyangan Catholic University, 2023)
These days, the industrialization era is rapidly developing and has impacted industrial relations disputes that are becoming increasingly complex and unavoidable. In the case of industrial relations disputes, difference in the decision between the first instance and the cassation level (there is no appeal for industrial relations disputes) occurs frequently. As such is the case between Siti Harini and PT Batik Danar Hadi, in which the verdicts of the first instance and cassation (Case Number: 37/Pdt.Sus-PHI/2017/PN.Smg and Case Number: 308 K/Pdt.Sus-PHI/2018) and the results of the previous first instance decisions (Case Number: 19/Pdt.Sus-PHI/2017/PN.Smg) differed from one another. In Case Number: 37/Pdt.Sus-PHI/2017/PN.Smg, Siti Harini's lawsuit was granted; in Case Number: 308K/Pdt.Sus-PHI/PN.Smg, PT Batik Danar Hadi's cassation application was granted; howeverin Case Number: 19/Pdt.Sus-PHI/2017/PN.Smg, Siti Harini's lawsuit was dismissed. If the lawsuit is filed while the case at hand is still in the middle of examination at the cassation level, it can be said that the suit is too early (premature) and consequently should be declared inadmissible (Niet Ontvankelijke Verklaard), but in fact it was granted instead. Hence, it can be concluded that there is an error in the judgment making. Conclusively, it can be stated that the implication of an error in the judgment in the first instance creates legal uncertainty and injustice in the decision.